Research Synthesis: Teacher Preparation for Rural Schools - Ellen Meier; Ervertt D. Edington (Journal of Research in Rural Education, 1983)
A review of the literature on teacher preparation and inservice programs in rural areas encompasses dilemmas facing rural education, what colleges and universities can do, and implications for colleges and universities. Part one describes dilemas. facing rural educators, not only in terms of class load, multiple preparations, extracurricular duties, etc., but also in terms of isolation and community problems such as cliques, gossip, and small town talk. Part two shows how colleges and universities can provide needed interventions for rural schools by assessing rural needs, providing special training programs for rural educators, bringing visibility of universities to rural communities, responding to rural needs, creating off-campus centers to more effectively meet teacher training needs, and building curriculum expertise. "Implications for Higher Education," part three, discusses expansion of the role of colleges and universities to include off-site training opportunities for preservice and inservice, shift in the role of the professors to "resource people for long- term staff development programs," creation of effective rural educator intervention models, and playing a more aggressive role in preparing teachers and administrators for rural areas. The conclusion stresses the need for colleges and universities to work directly with and in rural communities and maintain ongoing relationships with rural educators.